2017
DOI: 10.3758/s13421-017-0729-9
|View full text |Cite
|
Sign up to set email alerts
|

Do people use category-learning judgments to regulate their learning of natural categories?

Abstract: Although research has established that people can accurately judge how well they have learned categories, no research has examined whether people use their category-learning judgments (CLJs) to regulate their restudy of natural categories. Thus, in five experiments we investigated the relationship between people's CLJs and selections of categories for restudy. Participants first attempted to learn natural categories (bird families; e.g., finches, grosbeaks, and warblers) so that they could categorize new exemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…Since the study by Jacoby et al (2010), many researchers started using CLJs to examine how accurately people judge how well they know categories and how people use their CLJs to adjust their subsequent study in category learning. For example, Morehead et al (2017) examined whether people used their judgments to regulate their learning of natural categories. Five experiments showed that people indeed used their CLJs for restudy selections.…”
mentioning
confidence: 99%
“…Since the study by Jacoby et al (2010), many researchers started using CLJs to examine how accurately people judge how well they know categories and how people use their CLJs to adjust their subsequent study in category learning. For example, Morehead et al (2017) examined whether people used their judgments to regulate their learning of natural categories. Five experiments showed that people indeed used their CLJs for restudy selections.…”
mentioning
confidence: 99%
“…Despite the prior evidence, however, at least three recent studies have shown that some college students do the opposite (Morehead & Dunlosky, 2020;Morehead, Dunlosky, & Foster, 2017;Tullis & Benjamin, 2012); that is, they are more likely to choose to select to restudy materials with which they had given higher than lower JOLs. According to the contingent-efficacy hypothesis, selection strategies will moderate restudy efficacy (even when monitoring is highly accurate).…”
Section: Honor-dishonor Effectsmentioning
confidence: 92%
“…We then used the honor-dishonor method to evaluate whether participants effectively regulated their learning. We also investigated whether these differences in selection moderated the honor-dishonor advantage, given that prior research has demonstrated individual differences in study selections (Morehead et al, 2017).…”
Section: Present Investigationmentioning
confidence: 99%
“…To form the two strategy groups, any participant with a correlation between CLJs and selections at or below Ϫ.5 was classified as selecting less-well-learned categories (honor ϭ 71 participants; dishonor ϭ 72 participants), and any participant with a correlation at or above .5 was classified as selecting more-well-learned categories (honor ϭ 18 participants; dishonor ϭ 22 participants). The conservative cutoffs of .5 and Ϫ.5 were chosen to increase the likelihood that participants within these groups applied either the strategy to select the less-well-learned categories or the morewell-learned ones (as in Morehead et al, 2017). Participants with a correlation between Ϫ.5 and .5 were excluded from further analyses because 1 Correlations could not be computed for 30 participants because these participants gave the same CLJ for every category.…”
Section: Honor-dishonor Effects By Restudy Strategymentioning
confidence: 99%